A Systematic Review of Personalized Collaborative Systems - Neumayr, Thomas; Augstein, Mirjam (Frontiers in Computer Science, 2020)
Personalization, aiming at supporting users individually, according to their individual needs and prerequisites, has been discussed in a number of domains including learning, search, or information retrieval. In the field of Human-Computer Interaction, personalization also bears high potential as users might exhibit varying and strongly individual preferences and abilities related to interaction. For instance, there is a good amount of work on Personalized or Adaptive User Interfaces (also under the notion of Intelligent User Interfaces). Personalized Human-Computer Interaction, however, does not only subsume approaches to support the individual user, it also bears high potential if applied to collaborative settings, e.g., through supporting the individuals in a group as well as the group itself (considering all of its special dynamics). In collaborative settings (remote or co-located), there generally is a number of additional challenges related to human-to-human collaboration in a group, such as group communication, awareness or territoriality, device or software tool selection, or selection of collaborators. Personalized Collaborative Systems thus attempt to tackle many of these challenges. For instance, there are collaborative systems that recommend tools, content or team constellations. Such systems have been suggested in different domains and different collaborative settings and contexts. In most cases, these systems explicitly focus on a certain aspect of personalized collaboration support (such as team composition). This article provides a broader, concise overview of existing approaches to Personalized Collaborative Systems, based on a systematic literature review considering the ACM Digital Library.